Pelaksanaan Program Full Day School Dalam Mengembangkan Kecerdasan Spiritual SiswaThe Implementation of the Full Day School Program in Developing Students' Spiritual Intelligence - Dalimoenthe, Joya Kirana Angelin; Annur, Saipul; Kanada, Rabial (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to evaluate the implementation of the Full Day School Program at SMP LTI IGM Palembang in the context of developing students' spiritual intelligence. The program integrates religious spiritual activities, socio-religious activities, and religious ethics, focusing on character formation through worship routines, involvement in social activities, and the application of religious ethics. A qualitative research method was used to collect data through observation, interviews, and documentation. The results indicate that the program is effective in developing students' spiritual intelligence, with key strengths in routine practices such as Quranic recitation, congregational prayers, and social activities like morning charity. Positive impacts of the program include increased discipline, responsibility, and social awareness among students. However, challenges include student fatigue, potential boredom, and the need for improved time management. The study concludes that addressing these challenges could make the Full Day School Program a more optimal model for developing students' spiritual intelligence.